DIRAS2 modulates MAPK pathway–mediated ferroptosis to regulate excitation/inhibition balance and seizure susceptibility - Chenlu Zhang; Liqin Hu; Hui Zhang; Min Yang; Yuansong Zhang; Ningning Zhang; Yuanhang Xu; Yuping Zhao; Lingxin Ren; Haokun Guo; Wei Li; Xuefeng Wang; et al. (Proceedings of the National Academy of Sciences, 2026)
Epilepsy is a common neurological disorder that is widely believed to be associated with an imbalance between neuronal excitation and inhibition (E/I). DIRAS2, a Ras-related GTPase, has not been well understood regarding its role and function within the nervous system. In this study, we found that DIRAS2 is downregulated in the hippocampus during the epileptogenesis phase in a kainic acid-induced epilepsy model, while it is upregulated during the chronic phase in this epilepsy model and in patients with temporal lobe epilepsy. Overexpression of DIRAS2 alleviates epileptic seizure susceptibility and activity, whereas knockdown of DIRAS2 has an opposite effect. Whole-cell patch-clamp recordings reveal that DIRAS2 reduces the neuronal E/I ratio and alleviates neuronal hyperexcitability. Mechanistically, quantitative proteomic analysis reveals that ferroptosis is involved in mediating the effects of DIRAS2. Knockdown of DIRAS2 can exacerbate ferroptosis, while overexpression protects against ferroptosis in both in vivo and in vitro studies. Ferrostatin-1, a ferroptosis inhibitor, can rescue the E/I imbalance and epileptic behavioral changes induced by DIRAS2 knockdown. Finally, we found that DIRAS2 regulates ferroptosis by inhibiting the extracellular signal-regulated kinase/p38 mitogen-activated protein kinase pathway in epileptic mice. In summary, our study demonstrates the role of DIRAS2 in epilepsy and provides a potential target for epilepsy treatment.